MAKING LEARNING TEACHING MATERIALS IN SCHOOL BASED ON INFORMATION AND COMMUNICATION TECHNOLOGY - Tulus; Sawaluddin; Marpaung, T.J.; Syahputra, M.R. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
In the world of education now learning methods do not only use conventional methods such as from textbooks and teacher explanations, but also with effective and efficient learning methods using information technology. An example is multimedia-based learning media. Community service is one way that can be used to carry out information technology socialization. The community service that will be carried out in this study is entitled Easy and Interesting Mathematics Learning Through Animation. For elementary school students, with the aim of helping students in the learning process of mathematics that is more interesting interactive and fun, because in general lower elementary school students view mathematics lessons are difficult and boring learning. In this service, a learning media for mathematics will be created that includes the problem of building and space in accordance with the existing curriculum. Learning applications that are built include material, training, and tests, in accordance with applicable competency standards. Furthermore, training will be given to several elementary schools, as a briefing on how to use this learning system application so as to increase student motivation and ultimately improve student achievement and improve education quality.